The Investigation of Electrodiagnostic Findings in Patients with Nerve Injury Due to Earthquake: Single Centre Experience - Azize Esra Gürsoy; Şule Deveci; Dilara Mermi (Düzce Tıp Fakültesi Dergisi)
Aim: This study aimed to evaluate neuromuscular damage in the patients affected by the earthquakes that struck Kahramanmaraş, Türkiye.Material and Methods: Patients referred to the electrodiagnostic (EDx) laboratory between February and August 2023, who were trapped under rubble, were included in this study. Demographic data, clinical information (renal failure, serum creatine kinase level, and time spent under the rubble), and EDx results were analyzed.Results: Thirty-seven patients were included, while three patients with normal nerve conduction studies were excluded. Two (5.9%) of the 34 patients exhibited neurogenic and myogenic changes on EDx performed on days 24 and 25 post-trauma. In the remaining patients, neurogenic changes were observed, with 18 (52.9%) having peripheral nerve injury, 10 (29.4%) having plexopathy, 1 (2.9%) showing root involvement, and 5 (14.7%) of those with peripheral nerve injury presenting with complex involvement. Complete axonal damage was unrelated to the duration spent under the rubble (p=0.294). The presence of regeneration motor unit action potentials (MUAPs) was found statistically significantly related to the timing of the electromyography (EMG) performed (p=0.003), with the earliest regeneration findings observed on day 35. No statistically significant difference was found in the time spent under the rubble according to the regeneration presence (p=0.129).Conclusion: This study shows that earthquake injuries primarily result in multiple peripheral nerve injuries. The regeneration MUAP occurrence was not related to the duration spent under the rubble. In addition, myogenic and neurogenic MUAPs may appear on EMG in neurogenic injuries caused by compartment syndrome.